On agriculture - Ash, Harrison Boyd 1891-1944; Forster, E. S. (Edward Seymour), 1879-1950; Heffner, Edward H. (Edward Hoch), 1886-; Columella, Lucius Junius Moderatus (Cambridge (Mass.): Harvard University Press, 2006)
Columella (Lucius Iunius Moderatus) of Gades (Cadiz) lived in the reigns of the first emperors to about A.D. 70, coming early in life to Italy where he owned farms and lived near Rome. It is probable that he did military service in Syria and Cilicia and that he died at Tarentum. To one Publius Silvinus he addressed his Res Rustica the most comprehensive, systematic and detailed of Roman agricultural works: Book I Choice of farming-site; water-supply; buildings; staff. II Ploughing; fertilizing; care of crops. III, IV, V Cultivation, grafting and pruning of fruit trees ets., vines, olives. VI Acquisition, breeding, and rearing of oxen, horses, and mules; veterinary medicine. VII Sheep, goats, pigs, and dogs. VIII Poultry, fish-ponds. IX Bee-keeping. X (in hexameter poetry) Gardening, as an addition to the Georgics of Virgil who did not include it. At Silvinus' request Columella added XI Duties of the overseer of a farm; calendar for farm-work; more on gardening; and XII Duties of the overseer's wife; manufacture of wines; pickling; preserving. A XIIIth book is formed as a separate work by De Arboribus 'On Trees' (cp. Books III, IV, V) - on vines and olives and various trees, addressed it seems to Eprius Marcellus and forming perhaps part of an otherwise lost work written before the Res Rustica.
Volume 3: Books 10-12 ; On trees / with an English translation by E. S. Forster and Edward H. Heffner
Latin and English on opposite pages.
Includes bibliographical references (v. 1, p. xxiii-xxvii)-and indexes.
Latin text and English translation on opposite pages.
Keywords: Agriculture -- Early works to 1800.